2014
DOI: 10.1002/hc.21210
|View full text |Cite
|
Sign up to set email alerts
|

The Vinylic SN Reactions of Nitrodienes with Heteroatom‐Substituted Nuchleophilies and Their Structural Studies

Abstract: Herein, we report the reactions of 1,1,2,4,4‐pentachloro‐3‐nitro‐1,3‐butadiene 1a and (1Z)‐1‐bromo‐1,2,4,4‐tetrachloro‐3‐nitro‐1,3‐butadiene 1b with nitrogen‐ and sulfur‐containing nucleophiles to obtain highly functionalized S‐, S,S‐, S,S,S‐, S,O‐ and N,S‐substituted‐polyhalodiene‐3‐nitro‐1,3‐butadiene derivatives. Most of these reactions turned out to be highly selective with good to very good yields. All new compounds have been characterized by nuclear magnetic resonance spectroscopy, mass spectrometry, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Compounds 1a and 1b gave vinylic substitution reaction at room temperature and with the absence of solvent because of the reactivity of terminal carbon having nitrodichlorovinyl, and they yielded monosubstituted polyhalobutadiene compounds 3a [49] and 3b [50]. It has been reported that mono(thio)substitution nitrodienes are (E) isomers in previous studies [56][57][58]. As a consequence, it might be thought that derived new S-Substituted nitrodiene products were probably (E) isomers.…”
Section: Synthesis Of S-substituted Perhalonitrobuta-13-dienesmentioning
confidence: 99%
“…Compounds 1a and 1b gave vinylic substitution reaction at room temperature and with the absence of solvent because of the reactivity of terminal carbon having nitrodichlorovinyl, and they yielded monosubstituted polyhalobutadiene compounds 3a [49] and 3b [50]. It has been reported that mono(thio)substitution nitrodienes are (E) isomers in previous studies [56][57][58]. As a consequence, it might be thought that derived new S-Substituted nitrodiene products were probably (E) isomers.…”
Section: Synthesis Of S-substituted Perhalonitrobuta-13-dienesmentioning
confidence: 99%
“…Polyhalonitrobutadienes are valuable precursors for highly functionalized acyclic or (hetero)cyclic compounds. 1,3 Especially perchloro-2-nitrobutadiene (13) has often served as a starting material of choice, due to its enhanced reactivity in SNVin processes. 1,4 Thus, applying selective and mild reaction conditions, this diene enables 'click' chemistry type syntheses.…”
Section: Introductionmentioning
confidence: 99%
“…Substituted N ‐heterocycles, in particular, the six membered saturated ones as various morpholine, piperidine and piperazine analogs are undoubtedly a major theme in synthesis, being the key building blocks or sub‐units of complex molecular architectures of pharmacological activity used in psychological and neurological researching fields. Owing to their unique and versatile activities, there is a continuing care in this area of synthetic heterocyclic‐organic chemistry [12–20] . 2‐Nitroperchlorobutadiene 1 , the most important representative of pechloronitrobutadiene compound, serves as the starting material for generating new cyclic polysubstituted heterocycles.…”
Section: Introductionmentioning
confidence: 99%